2016
DOI: 10.1007/978-3-319-32144-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Compactness of Linearized Kinetic Operators

Abstract: International audienceThis article reviews various results on the compactness of the linearized Boltzmann operator and of its generalization to mixtures of non-reactive monatomic gases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…use (6) and (8) again, and the fact that Θ is an isometry. Note that, in both cases, the Jacobian of the changes of variables is 1.…”
Section: Computations Of the Maxwell-stefan Diffusion Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…use (6) and (8) again, and the fact that Θ is an isometry. Note that, in both cases, the Jacobian of the changes of variables is 1.…”
Section: Computations Of the Maxwell-stefan Diffusion Coefficientsmentioning
confidence: 99%
“…The linearized Boltzmann operator L can then be dened as in [5,8], so that L can be considered as an operator L 2 (R 3 ) I → L 2 (R 3 ) I with the standard Lebesgue product measure (without any weight). For any i, the i th component of Lg writes…”
Section: Computations Of the Maxwell-stefan Diffusion Coefficientsmentioning
confidence: 99%
“…Besides this, in [10] a new multi-species Carleman's representation and a new Povznertype inequality was proved, due to the loss of symmetry arisen from different masses. In [6,7], compactness of one part of the linearized multi-species operator was studied, moreover, in [4] it was shown that in the diffusive limit, the multi-species Boltzmann equation converges to the Maxwell-Stefan system. In [2], the Chapman-Enskog asymptotics for a mixture of gases was presented.…”
Section: State Of the Art On The Multi-species Deterministic Boltzmann Equationmentioning
confidence: 99%
“…We consider the multi-species Boltzmann equation describing the evolution of a multi-species mono-atomic nonreactive gaseous mixture with additional uncertainty coming from the initial data and collision kernel, which was studied analytically in the deterministic setting in [1,3,5,7,8,10,14]. Compared to the single-species deterministic analysis of the Boltzmann equation, dealing with different conserved quantities due to different thermodynamic properties of mixtures (see the multispecies H-theorem in [16,20]) provided the main difficulty in the analysis for the multi-species deterministic problem.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the multi-species Boltzmann equation describing the evolution of a multi-species mono-atomic nonreactive gaseous mixture with additional uncertainty coming from the initial data and collision kernel, which was studied analytically in the deterministic setting in [1,3,5,7,8,10,14]. Compared to the single-species deterministic analysis of the Boltzmann equation, dealing with different conserved quantities due to different thermodynamic properties of mixtures (see the multispecies H-theorem in [16,20]) provided the main difficulty in the analysis for the multi-species deterministic problem.…”
Section: Introductionmentioning
confidence: 99%